A Proposed Grading Scale for Predicting Outcomes After Stereotactic Radiosurgery for Dural Arteriovenous Fistulas. Issue 2 (4th October 2019) - Mohammed, Nasser; Hung, Yi-Chieh; Chen, Ching-Jen; Xu, Zhiyuan; Schlesinger, David; Kano, Hideyuki; Chiang, Veronica; Hess, Judith; Lee, John; Mathieu, David; Kaufmann, Anthony M; Grills, Inga S; et al.
Abstract: BACKGROUND: There are presently no grading scales that specifically address the outcomes of cranial dural arteriovenous fistula (dAVF) after stereotactic radiosurgery (SRS). OBJECTIVE: To design a practical grading system that would predict outcomes after SRS for cranial dAVFs. METHODS: From the International Radiosurgery Research Foundation (University of Pittsburgh [41 patients], University of Pennsylvania [6 patients], University of Sherbrooke [2 patients], University of Manitoba [1 patient], West Virginia University [2 patients], University of Puerto Rico [1 patient], Beaumont Health System 1 [patient], Na Homolce Hospital [13 patients], the University of Virginia [48 patients], and Yale University [6 patients]) centers, 120 patients with dAVF treated with SRS were included in the study. The factors predicting favorable outcome (obliteration without post-SRS hemorrhage) after SRS were assessed using logistic regression analysis. These factors were pooled with the factors that were found to be predictive of obliteration from 7 studies with 736 patients after a systematic review of literature. These were entered into stepwise multiple regression and the best-fit model was identified. RESULTS: Based on the predictive model, 3 factors emerged to develop an SRS scoring system: cortical venous reflux (CVR), prior intracerebral hemorrhage (ICH), and noncavernous sinus location. Class I (score of 0-1 points) predicted the best favorable outcome of 80%. Class II patients (2 points score) had an intermediate favorable outcome of 57%, and class III (score 3 points) had the least favorable outcome at 37%. The ROC analysis showed better predictability to prevailing grading systems (AUC = 0.69; P = .04). Kaplan–Meier analysis showed statistically significant difference between the 3 subclasses of the proposed grading system for post-SRS dAVF obliteration ( P = .001). CONCLUSION: The proposed dAVF grading system incorporates angiographic, anatomic, and clinical parameters and improves the prediction of the outcomes following SRS for dAVF as compared to the existing scoring systems.